2013
DOI: 10.1016/j.biomaterials.2012.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Melittin-grafted HPMA-oligolysine based copolymers for gene delivery

Abstract: Non-viral gene delivery systems capable of transfecting cells in the brain are critical in realizing the potential impact of nucleic acid therapeutics for diseases of the central nervous system. In this study, the membrane-lytic peptide melittin was incorporated into block copolymers synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization. The first block, designed for melittin conjugation, was composed of N-(2-hydroxypropyl)methacrylamide (HPMA) and pyridyl disulfide methacrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 46 publications
0
76
1
1
Order By: Relevance
“…This partial complexation can be attributed to the environmental pH, where most of the amine groups are deprotonated and surrounded by neutral HPMA units, and thus unable to interact with the DNA. On the other hand, the copolymers EPA 30 and EPA 10 were not able to bind DNA in any of the studied conditions (data not shown).…”
Section: Characterization Of Polymer/dna Polyplexescontrasting
confidence: 46%
See 1 more Smart Citation
“…This partial complexation can be attributed to the environmental pH, where most of the amine groups are deprotonated and surrounded by neutral HPMA units, and thus unable to interact with the DNA. On the other hand, the copolymers EPA 30 and EPA 10 were not able to bind DNA in any of the studied conditions (data not shown).…”
Section: Characterization Of Polymer/dna Polyplexescontrasting
confidence: 46%
“…Their galactosylated form has been evaluated in hepatocyte targeting gene therapy. Pun et al copolymerized HPMA with oligolysine methacrylamides to obtain oligocations randomly grafted on a neutral backbone, which exhibited a good cytotoxicity/transfection-efficiency balance, close to control PEI [9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…We have a long-standing interest in developing materials for gene delivery to the central nervous system (CNS) for potential treatment of neurodegenerative diseases. [11,45,46] Therefore, these three polyplexes containing the luciferase reporter gene were injected into the right lateral ventricle of mice. All the formulations were well tolerated and no significant gross morbidities or mortalities were observed due to polyplex injection.…”
mentioning
confidence: 99%
“…Importantly, the IC50 values for the cell parameters were lower than those obtained in the MTT and rat erythrocyte hemolytic assays, suggesting that these cellular changes ultimately brought about cell death. Although these data suggested that melittin and its analogs cannot be further developed Page 6 of 26 A c c e p t e d M a n u s c r i p t as oral PEs per se, prodrug modifications have recently enabled melittin to be used as part of a successful gene delivery construct when grafted onto N-(2-hydroxypropyl)methacrylamide (HPMA) and pyridyl disulfide methacrylamide (PDSMA) block copolymers, following intracerebral injection to mouse brain [44]. Elsewhere, formulation of melittin in the lipid membrane of a perfluorocarbon NP reduced systemic toxicity and permitted localization in mouse tumour cells [45].…”
Section: Hca: Cytotoxicity Of Polymers and Permeation Enhancersmentioning
confidence: 99%